Breathable cool sandwich composite cloth and production method thereof
By using a breathable cool sandwich composite cloth composed of the surface, intermediate and inner layer, combined with the preparation method of modified polyurethane fiber and the pretreatment technology of finishing liquid, the problem of insufficient breathability and thermal conductivity of the composite cloth is solved, and a strong cool effect and high wear comfort are achieved.
Patent Information
- Application Number
- CN202411746894.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing composite fabrics lack breathability and thermal conductivity, resulting in the inability to provide a cool feeling in high temperature environments, affecting the comfort of wearing.
The air-permeable cool sandwich composite cloth consisting of a surface layer, an intermediate layer and an inner layer is used. The surface layer is polypropylene fiber, the middle layer is modified polyurethane fiber, and the inner layer is a mixed fiber of polyester fiber and flax fiber. The thermal conductivity is improved by the preparation method of modified polyurethane fiber, and the inner layer fiber is pretreated through the finishing liquid to improve thermal conductivity.
The composite cloth has good breathability and strong coolness effect, which improves wear comfort and avoids the problem of decreasing the strength of polyurethane resin.
Smart Images

Figure BDA0005163963140000081 
Figure BDA0005163963140000091 
Figure BDA0005163963140000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite cloths, and in particular to a breathable cool sandwich composite cloth and a production method thereof. Background Art
[0002] With the continuous development of science and technology, textile fabrics that meet people's different needs emerge in an endless stream to meet the needs of consumers. However, the existing single-layer textile fabrics can no longer meet people's daily needs, so multi-layer composite fabrics have emerged.
[0003] Composite fabrics can be combined with different materials to give them multiple functions, such as waterproof and antibacterial, heat preservation, flame retardant, antistatic, radiation protection, etc. However, due to the multi-layer structure of composite fabrics, the breathability of composite fabrics will be poor, and the multi-layer structure will also lead to poor thermal conductivity of the fabrics. When used in high temperature environments, it cannot produce a cool feeling, resulting in reduced wearing comfort. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a breathable cool sandwich composite fabric and a production method thereof.
[0005] The technical solution of the present invention is: a breathable cool sandwich composite cloth, which is composed of a surface layer, a middle layer and an inner layer in a mass ratio of 1:0.5-0.7:1.1-1.3, wherein the surface layer is made of polypropylene fiber; the middle layer is made of modified polyurethane fiber; and the inner layer is made of polyester fiber and flax fiber mixed in a mass ratio of 7-8:2-3.
[0006] Description: The inner layer of the above-mentioned composite cloth is made of polyester fiber and flax fiber, which has good moisture absorption, can provide a cool feeling and is comfortable to wear. The middle layer is made of modified polyurethane fiber, which improves the thermal conductivity and allows heat to be dissipated quickly. The surface layer is made of polypropylene fiber to ensure the strength of the composite cloth. The composite cloth has good overall breathability, a strong cooling effect and high wearing comfort.
[0007] Furthermore, the preparation method of the modified polyurethane fiber comprises the following steps:
[0008] S1. Add nano-alumina and lauric acid into methanol and stir for 2 to 4 hours to obtain activated alumina; the mass ratio of nano-alumina, lauric acid and methanol is 1:0.2 to 0.4:4 to 6;
[0009] S2, adding the activated alumina to the acrylate, heating to 50-60°C under stirring, and then keeping the temperature to load the acrylate on the surface of the activated alumina for 30-40 minutes. After the heat preservation is completed, the alumina with the acrylate loaded on the surface is obtained; the mass ratio of the activated alumina to the acrylate is 1:5-8;
[0010] S3, adding polyurethane resin and aluminum oxide loaded with acrylate on the surface into a solvent, stirring for 10 to 15 minutes, adding an initiator into the solvent, reacting at 60 to 80° C. for 4 to 5 hours, grafting acrylate on the main chain of the polyurethane resin, and then evaporating and removing the solvent to obtain a modified polyurethane resin; the mass ratio of the polyurethane resin, aluminum oxide loaded with acrylate on the surface, initiator and solvent is 10 to 12: 0.2 to 0.5: 0.05 to 0.1: 100 to 200;
[0011] S4, melt spinning the modified polyurethane resin, the temperature during melt spinning is 200-220° C., and the winding speed is 1000-1200 m / min. After the melt spinning is completed, the modified polyurethane fiber is obtained.
[0012] Description: The above method activates nano-alumina. The surface of the activated alumina can adsorb acrylate, and then the acrylate can undergo in-situ polymerization under the action of an initiator to generate polyacrylate. At the same time, the acrylate can react with the polyurethane resin to graft the polyacrylate on the main chain of the polyurethane resin, thereby improving the binding property between the nano-alumina and the polyurethane resin and avoiding the decrease in the strength of the polyurethane resin. In addition, the nano-alumina improves the thermal conductivity and moisture absorption properties of the modified polyurethane fiber.
[0013] Further, in step S2, the preparation method of the acrylate is:
[0014] S2-1, adding p-tert-butylcatechol and acryloyl chloride into anhydrous ethanol to obtain a mixed solution; the mass ratio of p-tert-butylcatechol, acryloyl chloride and anhydrous ethanol is 1:0.6-0.8:6-9;
[0015] S2-2, cooling the mixed solution until the temperature of the mixed solution decreases by 5 to 10°C, adding pyridine to the mixed solution once, then stopping cooling and stirring the mixed solution until the temperature of the mixed solution rises by 3 to 6°C, and standing for 15 to 20 minutes; the initial temperature of the mixed solution is 25 to 30°C, and the single addition amount of pyridine accounts for 0.2 to 0.5% of the initial mass of the mixed solution;
[0016] S3-2, repeating step S2-2 until the temperature of the mixed solution drops to 0-5°C, and after standing for 1-2 hours, distilling the mixed solution to separate the acrylate.
[0017] Description: The above method uses tert-butylcatechol and acryloyl chloride to undergo an acylation reaction, and during the reaction, the temperature is gradually lowered to reduce the generation of by-products, and the temperature is waited to rise after each addition of pyridine to ensure that the pyridine is stably dispersed in the mixed solution, and finally an acrylate monomer containing a tert-butylcatechol group is prepared. The acrylate containing a tert-butylcatechol group has a stronger coordination ability and can effectively combine with the active sites on the activated alumina, thereby improving the binding property between the activated alumina and the acrylate.
[0018] Furthermore, in step S2, 3-isocyanatepropyltriethoxysilane is gradually added dropwise to the acrylate during the heating process, and the added amount of 3-isocyanatepropyltriethoxysilane accounts for 2-5% of the mass of the acrylate.
[0019] Note: Adding 3-isocyanatepropyltriethoxysilane can further improve the adsorption capacity of activated alumina for acrylate, so that the surface of activated alumina can fully adsorb acrylate.
[0020] Furthermore, in step S3, the solvent is any one of toluene, xylene or dimethylformamide, or a mixture of multiple solvents in any ratio.
[0021] Note: The above solvents have excellent solubility for polyurethane resin and can fully disperse aluminum oxide so that aluminum oxide is evenly distributed in the polyurethane resin.
[0022] Furthermore, in step S3, the initiator is ammonium persulfate or potassium persulfate.
[0023] Note: The above initiators can provide sufficient free radicals to initiate the polymerization reaction of acrylate.
[0024] Furthermore, in step S3, a citric acid solution with a mass concentration of 8 to 12% is added to the solvent every 50 to 60 minutes during the reaction process to adjust the pH value of the solvent to 5 to 6.
[0025] Note: Adding citric acid solution can ensure that the pH value in the solvent remains stable, so that the reaction is always carried out under the best conditions and the reaction can proceed fully.
[0026] On the other hand, the present invention provides a method for preparing a breathable cool sandwich composite fabric, which is used to prepare the breathable cool sandwich composite fabric, comprising the following steps:
[0027] Step 1, weaving polypropylene fibers to obtain a surface layer, weaving modified polyurethane fibers to obtain a middle layer, blending polyester fibers and flax fibers according to a mass ratio, and weaving to obtain an inner layer;
[0028] Step 2, immersing the inner layer in a finishing liquid for 30 to 40 minutes, the finishing liquid temperature is 50 to 60° C., and drying at 40 to 50° C. for 1 to 2 hours after immersion to obtain a pretreated inner layer;
[0029] Step 3: Coat both sides of the middle layer with polyurethane glue to a thickness of 20 to 30 μm, then place the inner layer and the surface layer on both sides of the middle layer respectively, and press them with a hot press to obtain a composite cloth; the pressing temperature is 120 to 140° C. and the pressure is 0.3 to 0.5 MPa.
[0030] Description: The above preparation method improves the thermal conductivity of the inner layer by finishing the inner layer, so that the heat of the inner layer can be dissipated outward through the middle layer, while the thermal conductivity of the surface layer is lower than that of the middle layer, so that when the composite cloth is worn, the heat of the inner layer can be fully conducted outward, while less environmental heat is conducted to the inner layer, effectively improving the cooling effect of the composite cloth.
[0031] Furthermore, the finishing liquid comprises, by weight, 3 to 6 parts of polyvinyl alcohol, 0.5 to 2 parts of sodium alginate, 1 to 5 parts of polyethylene glycol, 10 to 15 parts of menthol, 5 to 10 parts of palmitic acid, and 60 to 80 parts of deionized water.
[0032] Note: The finishing effect of the above finishing liquid is good, and it can be fully absorbed by the inner fiber, thereby improving the thermal conductivity of the inner fiber.
[0033] The beneficial effects of the present invention are:
[0034] (1) The inner layer of the composite cloth of the present invention is made of polyester fiber and flax fiber, which have good moisture absorption, can provide a cool feeling and is comfortable to wear. The middle layer is made of modified polyurethane fiber, which improves the thermal conductivity and allows heat to be quickly dissipated. The surface layer is made of polypropylene fiber to ensure the strength of the composite cloth. The composite cloth has good overall air permeability, a strong cooling effect and high wearing comfort.
[0035] (2) The present invention activates nano-alumina, and the surface of the activated alumina can adsorb acrylate, which can then undergo an in-situ polymerization reaction to generate polyacrylate. At the same time, polyacrylate is grafted onto the main chain of the polyurethane, thereby improving the binding properties of the nano-alumina and the polyurethane resin and avoiding a decrease in the strength of the polyurethane resin. The nano-alumina also improves the thermal conductivity and moisture absorption properties of the modified polyurethane fiber.
[0036] (3) The preparation method of the present invention improves the thermal conductivity of the inner layer by finishing the inner layer, so that the heat of the inner layer can be dissipated outward through the middle layer, while the thermal conductivity of the surface layer is lower than that of the middle layer. When the composite cloth is worn, the heat of the inner layer can be fully conducted outward, while less ambient heat is conducted to the inner layer, thereby effectively improving the cooling effect of the composite cloth. DETAILED DESCRIPTION
[0037] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0038] Embodiment 1: A breathable cool sandwich composite fabric, the composite fabric is composed of a surface layer, a middle layer and an inner layer in a mass ratio of 1:0.6:1.2, the surface layer is made of polypropylene fiber; the middle layer is made of modified polyurethane fiber; the inner layer is made of polyester fiber and flax fiber mixed in a mass ratio of 7.5:2.5;
[0039] The preparation method of the modified polyurethane fiber comprises the following steps:
[0040] S1. Add nano-alumina and lauric acid into methanol and stir for 3 hours to obtain activated alumina; the mass ratio of nano-alumina, lauric acid and methanol is 1:0.3:5;
[0041] S2, adding the activated alumina to the acrylate, heating to 55°C under stirring, gradually adding 3-isocyanate propyl triethoxy silane to the acrylate during the heating process, and then keeping the temperature to load the acrylate on the surface of the activated alumina, the temperature keeping time is 35 minutes, and after the temperature keeping is completed, the alumina with acrylate loaded on the surface is obtained; the mass ratio of the activated alumina to the acrylate is 1:7, and the amount of 3-isocyanate propyl triethoxy silane added accounts for 4% of the mass of the acrylate;
[0042] S3, adding polyurethane resin and aluminum oxide loaded with acrylate on the surface into a solvent, stirring for 12 minutes, adding an initiator into the solvent, reacting at 70°C for 4.5 hours, grafting acrylate on the main chain of the polyurethane resin, adding a citric acid solution with a mass concentration of 10% into the solvent every 55 minutes during the reaction to adjust the pH value of the solvent to 5.5, and then evaporating and removing the solvent to obtain a modified polyurethane resin; the mass ratio of polyurethane resin, aluminum oxide loaded with acrylate on the surface, initiator and solvent is 11:0.4:0.08:150; the solvent is dimethylformamide, and the initiator is ammonium persulfate;
[0043] S4, melt spinning the modified polyurethane resin, the temperature during melt spinning is 210° C., the winding speed is 1100 m / min, and after the melt spinning is completed, the modified polyurethane fiber is obtained;
[0044] The preparation method of the above acrylate is:
[0045] S2-1, adding p-tert-butylcatechol and acryloyl chloride into anhydrous ethanol to obtain a mixed solution; the mass ratio of p-tert-butylcatechol, acryloyl chloride and anhydrous ethanol is 1:0.7:8;
[0046] S2-2, cooling the mixed solution until the temperature of the mixed solution drops by 8°C, adding pyridine once to the mixed solution, then stopping cooling and stirring the mixed solution until the temperature of the mixed solution rises by 4°C, and standing for 18 minutes; the initial temperature of the mixed solution is 28°C, and the single addition amount of pyridine accounts for 0.3% of the initial mass of the mixed solution;
[0047] S3-2, repeating step S2-2 until the temperature of the mixed solution drops to 4°C, standing for 1.5 hours, and then distilling the mixed solution to obtain acrylate after separation;
[0048] The preparation method of the composite fabric comprises the following steps:
[0049] Step 1, weaving polypropylene fibers to obtain a surface layer, weaving modified polyurethane fibers to obtain a middle layer, blending polyester fibers and flax fibers according to a mass ratio, and weaving to obtain an inner layer;
[0050] Step 2, the inner layer is immersed in the finishing liquid for 35 minutes, the bath ratio during immersion is 1:12, the finishing liquid temperature is 55°C, and after immersion, it is dried at 45°C for 1.5 hours to obtain the pretreated inner layer;
[0051] Step 3, polyurethane glue is applied to both sides of the middle layer, the coating thickness of the polyurethane glue is 25 μm, and then the inner layer and the surface layer are placed on both sides of the middle layer respectively, and pressed by a hot press to obtain a composite cloth; the pressing temperature is 130° C. and the pressure is 0.4 MPa;
[0052] The ingredients of the finishing liquid include, by weight: 5 parts of polyvinyl alcohol, 1 part of sodium alginate, 3 parts of polyethylene glycol, 13 parts of menthol, 8 parts of palmitic acid, and 70 parts of deionized water.
[0053] Embodiment 2: This embodiment is basically the same as Embodiment 1, except that the inner layer is made of polyester fiber and flax fiber mixed in a mass ratio of 7:2.
[0054] Embodiment 3: This embodiment is basically the same as Embodiment 1, except that the inner layer is made of polyester fiber and flax fiber mixed in a mass ratio of 8:3.
[0055] Example 4: This example is basically the same as Example 1, except that the mass ratio of nano-alumina, lauric acid and methanol is 1:0.2:4.
[0056] Example 5: This example is basically the same as Example 1, except that the mass ratio of nano-alumina, lauric acid and methanol is 1:0.4:6.
[0057] Example 6: This example is basically the same as Example 1, except that the added amount of 3-isocyanatepropyltriethoxysilane is 2% of the mass of the acrylate.
[0058] Example 7: This example is basically the same as Example 1, except that the added amount of 3-isocyanatepropyltriethoxysilane is 5% of the mass of the acrylate.
[0059] Example 8: This example is basically the same as Example 1, except that the mass ratio of polyurethane, aluminum oxide loaded with acrylate on the surface, initiator and solvent is 10:0.2:0.05:100.
[0060] Example 9: This example is basically the same as Example 1, except that the mass ratio of polyurethane, aluminum oxide loaded with acrylate on the surface, initiator and solvent is 12:0.5:0.1:200.
[0061] Example 10: This example is basically the same as Example 1, except that an initiator is added to the solvent and the reaction is carried out at 60°C for 4.5 hours.
[0062] Example 11: This example is basically the same as Example 1, except that an initiator is added to the solvent and the reaction is carried out at 80°C for 4.5 hours.
[0063] Example 12: This example is basically the same as Example 1, except that the mixed solution is cooled until the temperature of the mixed solution drops by 5°C, pyridine is added once to the mixed solution, and then the cooling is stopped and the mixed solution is stirred until the temperature of the mixed solution rises by 3°C.
[0064] Example 13: This example is basically the same as Example 1, except that the mixed solution is cooled until the temperature of the mixed solution drops by 10°C, pyridine is added once to the mixed solution, and then the cooling is stopped and the mixed solution is stirred until the temperature of the mixed solution rises by 6°C.
[0065] Example 14: This example is basically the same as Example 1, except that the ingredients of the finishing liquid include, by mass, 3 parts of polyvinyl alcohol, 0.5 parts of sodium alginate, 1 part of polyethylene glycol, 10 parts of menthol, 5 parts of palmitic acid, and 60 parts of deionized water.
[0066] Example 15: This example is basically the same as Example 1, except that the ingredients of the finishing liquid include, by mass, 6 parts of polyvinyl alcohol, 2 parts of sodium alginate, 5 parts of polyethylene glycol, 15 parts of menthol, 10 parts of palmitic acid, and 80 parts of deionized water.
[0067] Comparative Example 1: Taking Example 1 as a reference, the middle layer is made of unmodified polyurethane fiber.
[0068] Comparative Example 2: Taking Example 1 as a reference, the nano-alumina was not activated and loaded with acrylate, but was directly added into the solvent.
[0069] Comparative Example 3: Taking Example 1 as a reference, the nano-alumina was not activated and acrylate was directly loaded.
[0070] Comparative Example 4: Using Example 1 as a reference, pyridine was added without waiting for the mixed solution temperature to rise.
[0071] Comparative Example 5: Using Example 1 as a reference, a commercially available acrylate monomer is used to replace the acrylate of the present application.
[0072] Comparative Example 6: Using Example 1 as a reference, the inner layer is not finished.
[0073] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the composite fabric, the coolness coefficient of the composite fabric of each embodiment was tested according to GB / T35263-2017, and the specific exploration is as follows:
[0074] Experimental Example 1: Investigating the influence of inner layer composition on composite fabric performance
[0075] Using Examples 1, 2, 3 and Comparative Example 1 as experimental comparisons, the properties of the composite fabrics with different inner layer compositions are shown in Table 1 below:
[0076] Table 1 Properties of composite fabrics with different inner layer compositions
[0077] Group Coolness coefficient Example 1 0.456 Example 2 0.441 Example 3 0.438 Comparative Example 1 0.285
[0078] It can be seen from the data in Table 1 that compared with Examples 1, 2, and 3, the composite fabric of Example 1 has the highest cooling coefficient, indicating that the composite fabric of Example 1 has the best cooling effect. This may be because the inner layer component of Example 1 has the best thermal conductivity, so the inner layer component selected in Example 1 is optimal.
[0079] Compared with comparative example 1, after the middle layer of Example 1 adopts unmodified polyurethane fiber, the coolness coefficient of the composite cloth is significantly reduced. This may be because the thermal conductivity of the composite cloth deteriorates after the unmodified polyurethane fiber is adopted.
[0080] Experimental Example 2: Investigating the effect of the ratio of nano-alumina, lauric acid and methanol on the performance of composite fabrics
[0081] Using Examples 1, 4, 5 and Comparative Examples 2 and 3 as experimental comparisons, the properties of the composite fabrics obtained under different ratios of nano-alumina, lauric acid and methanol are shown in Table 2 below:
[0082] Table 2 Properties of composite fabrics with different ratios of nano-alumina, lauric acid and methanol
[0083] Group Coolness coefficient Example 1 0.456 Example 4 0.428 Example 5 0.433 Comparative Example 2 0.326 Comparative Example 3 0.379
[0084] It can be seen from the data in Table 2 that compared with Examples 1, 4, and 5, the composite fabric of Example 1 has the highest cooling coefficient, indicating that the composite fabric of Example 1 has the best cooling effect. This may be because under the ratio of nano-alumina, lauric acid, and methanol in Example 1, the activated alumina surface has the most adsorption points, which can fully adsorb acrylate, so that the nano-alumina can be fully dispersed in the polyurethane fiber. Therefore, the ratio of nano-alumina, lauric acid, and methanol selected in Example 1 is optimal;
[0085] Compared with Comparative Examples 2 and 3, in Example 1, the coolness coefficient of the composite cloth is significantly reduced after the nano-alumina is not activated and loaded with acrylate. After the nano-alumina is not activated and directly loaded with acrylate, the coolness coefficient of the composite cloth is increased, but it is still lower than the composite cloth of Example 1. This may be because after the nano-alumina is activated, the surface of the nano-alumina can fully adsorb acrylate, so that the nano-alumina can be fully dispersed in the polyurethane fiber.
[0086] Experimental Example 3: Investigating the effect of the amount of 3-isocyanatepropyltriethoxysilane added on the properties of the composite fabric
[0087] Using Examples 1, 6, and 7 as experimental comparisons, the properties of the composite fabrics obtained at different addition amounts of 3-isocyanatepropyltriethoxysilane are shown in Table 3 below:
[0088] Table 3 Properties of composite fabrics with different addition amounts of 3-isocyanatepropyltriethoxysilane
[0089] Group Coolness coefficient Example 1 0.456 Example 6 0.429 Example 7 0.459
[0090] It can be seen from the data in Table 3 that as the amount of 3-isocyanatepropyltriethoxysilane added increases, the cool coefficient of the composite cloth gradually increases, among which the composite cloth of Example 1 has the highest cool coefficient. As the amount of 3-isocyanatepropyltriethoxysilane added continues to increase, the cool coefficient of the composite cloth begins to have no obvious change. This may be because the acrylate adsorbed on the surface of the activated alumina reaches a maximum value. Therefore, the amount of 3-isocyanatepropyltriethoxysilane added selected in Example 1 is optimal.
[0091] Example 4: Investigating the effects of the ratio of polyurethane, alumina loaded with acrylate on the surface, initiator and solvent on the properties of composite fabric
[0092] Using Examples 1, 8, and 9 as experimental comparisons, the properties of the composite fabrics obtained under different ratios of polyurethane, aluminum oxide loaded with acrylate on the surface, initiator, and solvent are shown in Table 4 below:
[0093] Table 4 Properties of composite fabrics of polyurethane, aluminum oxide loaded with acrylate on the surface, initiator and solvent at different ratios
[0094]
[0095]
[0096] It can be seen from the data in Table 4 that the composite fabric of Example 1 has the highest cooling coefficient, indicating that the composite fabric of Example 1 has the best cooling effect. This may be because the polyurethane, alumina loaded with acrylate on the surface, and the ratio of initiator to solvent in Example 1 allow the acrylate and polyurethane to react most fully. Therefore, the polyurethane, alumina loaded with acrylate on the surface, and the ratio of initiator to solvent selected in Example 1 are optimal.
[0097] Example 5: Investigating the effect of reaction temperature on the properties of composite fabrics
[0098] Using Examples 1, 10, and 11 as experimental comparisons, the properties of the composite fabrics at different reaction temperatures are shown in Table 5 below:
[0099] Table 5 Composite fabric properties at different reaction temperatures
[0100] Group Coolness coefficient Example 1 0.456 Example 10 0.442 Embodiment 11 0.445
[0101] It can be seen from the data in Table 5 that the composite fabric of Example 1 has the highest cooling coefficient, indicating that the composite fabric of Example 1 has the best cooling effect. This may be because at the reaction temperature of Example 1, the acrylate can fully undergo polymerization reaction and be grafted onto the polyurethane, so the reaction temperature selected in Example 1 is optimal.
[0102] Example 6: Investigating the effect of acrylic acid ester preparation temperature on the properties of composite fabrics
[0103] Using Examples 1, 12, 13 and Comparative Examples 4 and 5 as experimental comparisons, the properties of the composite fabrics obtained at different preparation temperatures of acrylic acid ester are shown in Table 6 below:
[0104] Table 6 Properties of acrylic composite fabrics prepared at different temperatures
[0105]
[0106]
[0107] It can be seen from the data in Table 6 that compared with Examples 1, 12, and 13, the composite fabric of Example 1 has the highest cooling coefficient, indicating that the composite fabric of Example 1 has the best cooling effect. This may be because at the acrylate preparation temperature of Example 1, the yield of acrylate containing tert-butyl catechol is higher and the by-products are less, so the acrylate preparation temperature selected in Example 1 is optimal;
[0108] Compared with Comparative Example 4, after adding pyridine, the coolness coefficient of the composite cloth was significantly reduced without waiting for the temperature of the mixed solution to rise. This may be because the pyridine was not stably dispersed in the mixed solution without waiting for the temperature to rise, which affected the yield of the acrylate containing tert-butyl catechol groups.
[0109] Compared with Comparative Example 5, Example 1 shows that the coolness coefficient of the composite cloth is significantly reduced after using the commercially available acrylate monomer. This may be because the coordination ability between the acrylate without tert-butylcatechol group and the activated alumina is poor and cannot be fully combined with the activated alumina.
[0110] Example 7: Investigating the effect of finishing liquid composition on composite fabric performance
[0111] Using Examples 1, 14, 15 and Comparative Example 6 as experimental comparisons, the properties of the composite fabrics under different finishing liquid compositions are shown in Table 7 below:
[0112] Table 7 Properties of composite fabrics under different finishing liquid compositions
[0113] Group Coolness coefficient Example 1 0.456 Embodiment 14 0.446 Embodiment 15 0.441 Comparative Example 6 0.425
[0114] From the data in Table 7, it can be seen that compared with Examples 1, 14, and 15, the composite fabric of Example 1 has the highest cooling coefficient, indicating that the composite fabric of Example 1 has the best cooling effect. This may be because under the finishing liquid composition of Example 1, the inner layer fiber has the best absorption effect on the finishing liquid, so the finishing liquid composition selected in Example 1 is optimal;
[0115] Compared with Comparative Example 6, in Example 1, the coolness coefficient of the composite fabric decreased after the inner layer was not finished, which indicates that the coolness finishing can improve the coolness coefficient of the composite fabric.
Claims
1. A breathable cool sandwich composite fabric, characterized in that: The composite cloth is composed of a surface layer, a middle layer and an inner layer in a mass ratio of 1:0.5-0.7:1.1-1.3, wherein the surface layer is made of polypropylene fiber; the middle layer is made of modified polyurethane fiber; and the inner layer is made of a mixture of polyester fiber and flax fiber in a mass ratio of 7-8:2-3.
2. The breathable cool sandwich composite fabric according to claim 1, characterized in that: The preparation method of the modified polyurethane fiber comprises the following steps: S1. Add nano-alumina and lauric acid into methanol and stir for 2 to 4 hours to obtain activated alumina; the mass ratio of nano-alumina, lauric acid and methanol is 1:0.2 to 0.4:4 to 6; S2, adding the activated alumina to the acrylate, heating to 50-60°C under stirring, and then keeping the temperature to load the acrylate on the surface of the activated alumina for 30-40 minutes. After the heat preservation is completed, the alumina with the acrylate loaded on the surface is obtained; the mass ratio of the activated alumina to the acrylate is 1:5-8; S3, adding polyurethane resin and aluminum oxide loaded with acrylate on the surface into a solvent, stirring for 10 to 15 minutes, adding an initiator into the solvent, reacting at 60 to 80° C. for 4 to 5 hours, grafting acrylate on the main chain of the polyurethane resin, and then evaporating and removing the solvent to obtain a modified polyurethane resin; the mass ratio of the polyurethane resin, aluminum oxide loaded with acrylate on the surface, initiator and solvent is 10 to 12: 0.2 to 0.5: 0.05 to 0.1: 100 to 200; S4, melt spinning the modified polyurethane resin, the temperature during melt spinning is 200-220° C., and the winding speed is 1000-1200 m / min. After the melt spinning is completed, the modified polyurethane fiber is obtained.
3. The breathable cool sandwich composite fabric according to claim 2, characterized in that: In step S2, the preparation method of the acrylate is: S2-1, adding p-tert-butylcatechol and acryloyl chloride into anhydrous ethanol to obtain a mixed solution; the mass ratio of p-tert-butylcatechol, acryloyl chloride and anhydrous ethanol is 1:0.6-0.8:6-9; S2-2, cooling the mixed solution until the temperature of the mixed solution decreases by 5 to 10°C, adding pyridine to the mixed solution once, then stopping cooling and stirring the mixed solution until the temperature of the mixed solution rises by 3 to 6°C, and standing for 15 to 20 minutes; the initial temperature of the mixed solution is 25 to 30°C, and the single addition amount of pyridine accounts for 0.2 to 0.5% of the initial mass of the mixed solution; S3-2, repeating step S2-2 until the temperature of the mixed solution drops to 0-5°C, standing for 1-2 hours, and then distilling the mixed solution to obtain acrylate after separation.
4. The breathable cool sandwich composite fabric according to claim 2, characterized in that: In step S2, 3-isocyanatepropyltriethoxysilane is gradually added dropwise to the acrylate during the heating process, and the added amount of 3-isocyanatepropyltriethoxysilane accounts for 2-5% of the mass of the acrylate.
5. The breathable cool sandwich composite fabric according to claim 2, characterized in that: In step S3, the solvent is any one of toluene, xylene or dimethylformamide, or a mixture of multiple solvents in any ratio.
6. The breathable cool sandwich composite fabric according to claim 2, characterized in that: In step S3, the initiator is ammonium persulfate or potassium persulfate.
7. The breathable cool sandwich composite fabric according to claim 2, characterized in that: In step S3, during the reaction process, a citric acid solution with a mass concentration of 8 to 12% is added to the solvent every 50 to 60 minutes to adjust the pH value of the solvent to 5 to 6.
8. A method for preparing a breathable cool sandwich composite fabric, for preparing the breathable cool sandwich composite fabric as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, weaving polypropylene fibers to obtain a surface layer, weaving modified polyurethane fibers to obtain a middle layer, blending polyester fibers and flax fibers according to a mass ratio, and weaving to obtain an inner layer; Step 2, immersing the inner layer in a finishing liquid for 30 to 40 minutes, the finishing liquid temperature is 50 to 60° C., and drying at 40 to 50° C. for 1 to 2 hours after immersion to obtain a pretreated inner layer; Step 3: Coat both sides of the middle layer with polyurethane glue to a thickness of 20 to 30 μm, then place the inner layer and the surface layer on both sides of the middle layer respectively, and press them with a hot press to obtain a composite cloth; the pressing temperature is 120 to 140° C. and the pressure is 0.3 to 0.5 MPa.
9. The method for preparing the breathable cool sandwich composite fabric according to claim 8, characterized in that: The finishing liquid comprises, by weight, 3 to 6 parts of polyvinyl alcohol, 0.5 to 2 parts of sodium alginate, 1 to 5 parts of polyethylene glycol, 10 to 15 parts of menthol, 5 to 10 parts of palmitic acid and 60 to 80 parts of deionized water.
Citation Information
Patent Citations
Nano modified organosilicon acroleic acid polyurethane coating and preparation
CN101481581A
Ventilating and comfortable fabric
CN102935736A
Cool and breathable textile fabric and preparation method thereof
CN106985471A
High-elasticity skin-friendly fabric and preparation method thereof
CN117584556A
Cool fabric based on modified polyester fibers
CN217677966U